Efektifitas Penambahan Insulin dalam Media Maturasi dan atau Media Kultur pada Tingkat Maturasi Oosit dan Perkembangan Awal Embrio Sapi secara In Vitro - Ni Wayan Kurniani Karja; Syafri Nanda; Mohamad Agus Setiadi (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2019)
This study was aimed to determine the effect of insulin supplementation in maturation and/or culture medium on nuclear maturation rate and the early bovine embryo development in vitro. Oocytes were collected and matured in maturation media without (IVM I-) or with (IVM I+) 10 ug/µL insulin at incubator 5% CO2 and the temperature of 39 °C, for early embryonic development evaluation, oocytes were divided into 4 groups, without the supplementation of insulin to the maturation medium and culture (IVM I-/IVC I-), insulin supplementation only the maturation medium (IVM I+/IVC I-), insulin supplementation only in the culture medium (IVM I-/IVC I+), and the combination of insulin supplementation to the maturation medium and culture (IVM I+/IVC I+). The result showed that supplementation of insulin to the maturation medium increased number nuclear maturation was higher 87.7% (P<0.05) compared to treatment without supplementation of insulin (70.1%). Cleavage rate in treatment IVM was higher IVM I-/IVC I- (55.8%), IVM I+/IVC I- (64.1%), IVM I-/IVC I+ (59.9%) (P<0.05). Result of the other were showed that early bovine embryo on day-4 cultured (IVC) reached 16 cell on treatment IVM I-/IVC I+(31,9%) and IVM I+/IVC I+ (27,1%) were higher compared to treatment IVM I-/IVC I-(2.9%) and IVM I+/IVC I- (2.5%) (P<0.05). In conclusion, supplementation of insulin to maturation medium and culture medium can increase nuclear maturation rate and improved early embryo cleavage rate.